Impact of Smoking on Oral Mucosa: A Case Report - Nurfianti; Shafa Adinda Rizkhi Nurpratama; Audiawati; Ahmad Ronal; Faezah Rokhani; Aspalilah Alias (Faculty of Dentistry, YARSI University, 2024)
Non-Indexed Publication